Characterization of the Early Life Microbiota Development and Predominant Lactobacillus Species at Distinct Gut Segments of Low- and Normal-Birth-Weight Piglets - Li, Na; Huang, Shimeng; Jiang, Lili; Dai, Zhaolai; Li, Tiantian; Han, Dandan; Wang, Junjun (Frontiers in Microbiology, 2019)
Microbial exposure during early life plays a pivotal role in modulating the health and intestinal development of the host. Our recent study showed that the low-birth-weight (LBW) piglets harbored a different fecal microbiota compared to normal-birth-weight (NBW) piglets during early life with a lower abundance of the genus Lactobacillus. Considering the spatial variations in gut microbiota at distinct gut locations, this study was designed to further investigate the differences in the microbiota composition and predominant Lactobacillus species in the ileum and colon between LBW and NBW piglets during early life, including day 7 (D7), day 21 (D21, before weaning), and day 35 (D35, two weeks after weaning). Compared with the normal group, LBW piglets harbored a significantly lower proportion of short-chain fatty acids (SCFAs)-producing microbes, such as Ruminococcaceae and Prevotellaceae in the ileum on D7, Alistipes and Lachnospiraceae in the colon on D7, Blautia in the colon on D21, and Ruminiclostridium 9 in the colon on D35. The relative abundance of the phylum Bacteroidetes was also declined in both ileum and colon of LBW piglets on D7. Meanwhile, the levels of total short-chain fatty acids on D7, D21, and D35, acetic and valeric acid on D7 and D21, propionic acid on D21, and lactic acid on D21 and D35, were also declined in the colon of LBW piglets. Moreover, functional alterations in the gut microbiota of LBW piglets were characterized by differentially abundant microbial genes involved in multiple pathways such as amino acid metabolism, energy metabolism, replication and repair, and metabolism of cofactors and vitamins in the colon. Additionally, lower numbers of L. salivarius on D7 and L. amylovorus on D21 resided in the colon of LBW piglets compared to those in the normal ones. Collectively, LBW piglets have altered bacterial communities, microbial metabolism and gene functions in the ileum and colon during early life, especially the colonic community. This work will help to develop novel ideas in identifying the reliable biomarkers affecting the gut microbiota development in LBW piglets during early life and facilitate the development of new nutritional interventions.